Treatment of the complicated course ORI by means of natural origin - I. N. Kholodova; I. N. Zakharova; Y. I. Ivakhnenko (Медицинский совет, 2017)
In the article the authors consider the problem of treatment of the complicated course of acute respiratory infection (ARI) by natural origin drugs. The efficacy and adverse reactions of official medicine drugs and complex homeopathic medicines are discussed. The basic principles of homeopathic treatment are set forth. Data of international and Russian researchers are provided to prove the feasibility and effectiveness of treating symptoms of cough and rhinitis by natural origin drugs. Schemes of treatment by the example of some complex homeopathic preparations are proposed.